Perspectives of Supervisors on the Diploma in Nursing Graduates' Performance in Selected Healthcare Facilities of Malawi: A Qualitative Tracer Study. - Mkwinda, Esmie; Mugala, Zione; Jere, Jester; Jere, Treazer; Muthali, Chimwemwe; Mselema, Catherine Titanus; Banda, Merium Kalyolyo; Chironda, Geldine (Africa Journal of Nursing & Midwifery, 2025)
Tracer studies are essential for understanding the relevance and quality of programmes offered by universities and the labour market. Saint John of God College of Health Sciences (SJOGCHS) introduced the Diploma in Nursing programme in 2014 and is committed to producing competent graduates who meet employer expectations. This study explored the supervisors' views on the performance of the SJOGCHS diploma in nursing graduates in selected healthcare facilities in Malawi. An explorative research design that followed a qualitative approach was used to collect data from the immediate supervisors of the graduates using individual interviews. Data were collected from thirteen (13) participants in eight (8) government and private healthcare facilities using a semi-structured in-depth interview guide and analysed using a content analysis guide. Findings revealed that graduates performed several nursing roles like basic and mental health care, teaching students, supervising junior staff, ward management and quality assurance activities. These roles were performed with minimal supervision, while other graduates performed beyond expectations. Supervisors noted that graduates had gaps in managing obstetrics and gynaecological cases, professionalism, delegation and ward management. The study recommended that SJOGCHS should introduce a generic training programme with both nursing and midwifery components and an upgrading programme in midwifery to improve care of obstetric and gynaecological patients and their employability. Furthermore, students in these programmes would need frequent supervision in the clinical area and innovative delivery of management and leadership courses.